Development of Pre-engineered Geomaterial for Use in Road Embankment and Retaining Structure Backfill - A. Naser Abdul Ghani; Fauziah Ahmad; Rosli Hamir; Sabarudin Mohd (2005)
Load reduction effect of using lightweight material in new construction, expansion, rehabilitation or maintenance of transportation facilities provide advantages in term of reduction of total cost, construction time and maintenance work especially in soft ground areas. Lightweight geomaterial composite with controllable geotechnical properties were developed and tested in laboratory. The results indicated that, design mix of the geomaterial composite has significant influence on its strength, elasticity and deformation characteristics. (Authors' abstract)